Life cycle modeling of a wind powered car carrier - Carlsson, Josef; Olsson, Tobias (My University, 2020)
Emissions leading to global warming must be addressed by all industries and IMO has set a goal to reduce annual GHG emissions from international shipping by at least 50% by 2050. Possible pathways to achieve this are selecting a less carbon intensive fuel, reducing the average speed, or by reducing fuel consumption by applying fuel saving technologies. This thesis investigates all three concepts as applied to an ocean-going car carrier and applies two methodologies, LCA and LCC, to investigate the potential gains of wind propulsion. To determine and compare the performance of wind propulsion to ships using only renewable fuels, a ship without sails fuelled by LNG is used as a baseline. Total GHG emissions as well as annual and total cost of ownership is significantly reduced by combining free and abundant wind with modern ship construction. Using a preliminary performance routing in the North Atlantic, the wind powered car carrier can reduce fuel consumption by 80% compared to a ship without sails using the same hull. Although the addition of a wind propulsion system comes at a higher initial investment cost and increased GHG emissions from construction and scrapping, the reduction in fuel consumption creates significant financial and environmental gains. Of the investigated fuel options (LBG, BioMeOH and LNG), only the BioMeOH fuelled ship has life cycle GHG emissions reductions in the same range as the wind powered car carrier (using LNG), but with significantly higher operational cost. LBG is only marginally better than LNG from a short-term perspective (GWP20) and comes at a considerably higher cost of averting GHG emissions than BioMeOH because it emit at least three times as much GHGs. Only the wind powered car carrier offers a negative abatement cost of averting GHG emissions.
Keywords: Sustainable shipping, LCA, LCC, abatement cost, climate impact, wind propulsion system, alternative fuel, wPCC, marine transportation.